Evaluation of the Functional Properties and Edible Safety of Concocted Xanthii Fructus Protein - Yuchen Dong; Zihao Wan; Fuguo Han; Xuemei Fan; Yanli Hao; Fang Wei; Qingfei Liu (Foods)
Xanthii Fructus (XF) not only has medicinal function in traditional Chinese medicine (TCM) but also contains rich oil and protein. The aim of this research was to develop the edible value of its protein based on the investigation on the extraction, basic characteristics and functions, safety, gut microbiota, and metabolomics, especially the effect of the concocting process. The proteins from raw and concocted XF were prepared using two methods: alkaline solubilization followed by acid precipitation and ammonium sulfate salting-out, respectively. The secondary structure and physicochemical properties of the proteins were characterized through spectroscopic analysis and property determination. The effects of alkaline and the concocting process on the proteins were systematically compared. The results indicated that the salting-out method could retain the protein activity better. Both alkali treatment and the concocting process altered the folding state of proteins. The toxicological results in mice indicated that a high dose (0.35 g/kg) of raw Xanthii Fructus protein (XFP) might cause damage to the liver and small intestine, and the concocting process could significantly alleviate the damage. The 16S rRNA sequencing technology was used to untangle their impact on gut microbiota in mice and the result showed that raw protein had a certain regulatory effect on Bifidobacterium, Rhodococcus, Lactococcus, and Clostridium, while the concocted protein had a smaller impact, mainly affecting Bacteroides and Bifidobacterium. The untargeted metabolomics using liquid chromatography-mass spectrometry (LC-MS) showed that the proteins of raw XF affected the metabolic level through cysteine and methionine metabolism, purine metabolism, amino sugar and nucleotide sugar metabolism pathways, and the concocted protein mainly involved histidine metabolism and purine metabolism pathways. Overall, XFP had potential development prospects, but the anti-nutritional factors might have some toxicity. The concocting process could significantly improve its safety, and the concocted proteins were worth developing as a food source. In the future, the processing conditions should be further optimized and more systematic investigation should be performed to ensure the safety of XF as a food source.